2013
DOI: 10.1002/grl.50304
|View full text |Cite
|
Sign up to set email alerts
|

The Beijing extreme rainfall of 21 July 2012: “Right results” but for wrong reasons

Abstract: [1] The heaviest rainfall in 6 decades fell in Beijing on 21 July 2012 with a record-breaking amount of 460 mm in 18 h and hourly rainfall rates exceeding 85 mm. This extreme rainfall event appeared to be reasonably well predicted by current operational models, albeit with notable timing and location errors. However, our analysis reveals that the model-predicted rainfall results mainly from topographical lifting and the passage of a cold front, whereas the observed rainfall was mostly generated by convective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 18 publications
(22 reference statements)
4
88
0
Order By: Relevance
“…The frequent occurrence of rainfall extremes produces multiple disasters, including urban flooding, server soil erosion, landslides and debris flows [1]. Moreover, rainfall extremes affect the ecological process of the terrestrial ecosystem [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The frequent occurrence of rainfall extremes produces multiple disasters, including urban flooding, server soil erosion, landslides and debris flows [1]. Moreover, rainfall extremes affect the ecological process of the terrestrial ecosystem [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…On 21 July 2012, however, the heaviest daily total rainfall since 1976 occurred in Beijing and the adjacent areas. This rainstorm event had a regional average of 190.3 mm (far more than the climatological mean of 160.5 mm in July) in the Beijing area and an amount of 24 h accumulated 460 mm (nearly equal to the local annual precipitation of 542 mm) and an hourly rainfall above 85 mm in the western mountain area of Beijing [ Zhang et al ., ; Zhou et al ., ]. Some studies showed that this rainstorm consisted of two different stages: the first prefrontal heavy rainfall stage with topographical lifting, easterly winds in the local early afternoon, and northwesterly winds in the local evening; and the second frontal but relatively weak rainfall stage at night, as a large‐scale cold front approached Beijing [ Sun et al ., ; Zhang et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…This rainstorm event had a regional average of 190.3 mm (far more than the climatological mean of 160.5 mm in July) in the Beijing area and an amount of 24 h accumulated 460 mm (nearly equal to the local annual precipitation of 542 mm) and an hourly rainfall above 85 mm in the western mountain area of Beijing [ Zhang et al ., ; Zhou et al ., ]. Some studies showed that this rainstorm consisted of two different stages: the first prefrontal heavy rainfall stage with topographical lifting, easterly winds in the local early afternoon, and northwesterly winds in the local evening; and the second frontal but relatively weak rainfall stage at night, as a large‐scale cold front approached Beijing [ Sun et al ., ; Zhang et al ., ]. Because of its high impact and extreme rainfall event, several studies of this Beijing rainstorm have been published [e.g., Chen et al ., ; Sun et al ., ; Zhang et al ., ; Zhao et al , ; Du et al ., ; Jiang et al ., ; Ran et al ., ; Xu et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…But to what extent is this phenomenon caused by Beijing's rapid urbanization and land use change? A few studies have examined the causes and predictability of Rainstorm 721 [e.g., Zhang et al, 2013;Zhou et al, 2013;Sun et al, 2013], which together suggest that the convective cells were triggered by local topography and propagated with the large-scale weather system [Zhang et al, 2013;Sun et al, 2013]. These studies, however, have paid little attention to the possible impact of urbanization on this rainfall event.…”
mentioning
confidence: 99%